(3TQM bWQ GdfOi hHd GdUOis - (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, J (B761 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYGde GHf gTGe GdCfUGQi GdMeO ddg QGaY GdOQLGJ def EfNaV dLdGdg hHYO agPg fcJ MQQJgG Ydi ebOeJi GdeSeGI HbWQ GdfOi hHd GdUOi s
(3BNQgG (B:s
(3hgPG BNQ eG CQOfG EedGAg Ydi gPg GdebOeI , hbO LGA HYhf Gddg egPH GdeHGfi eTjO GdeYGfi hMSHfG Gddg hfYe Gdhcjd hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3Hg eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B465s
Keywords: (3GdfMhs